Evaluation of Leading Smartwatches for the Detection of Hypoxemia: Comparison to Reference Oximeter - Walzel, Simon; Mikus, Radek; Rafl-Huttova, Veronika; Rozanek, Martin; Bachman, Thomas E; Rafl, Jakub (Sensors, 2023)
Although smartwatches are not considered medical devices, experimental validation of their accuracy in detecting hypoxemia is necessary due to their potential use in monitoring conditions manifested by a prolonged decrease in peripheral blood oxygen saturation (SpO2), such as chronic obstructive pulmonary disease, sleep apnea syndrome, and COVID-19, or at high altitudes, e.g., during sport climbing, where the use of finger-sensor-based pulse oximeters may be limited. The aim of this study was to experimentally compare the accuracy of SpO2 measurement of popular smartwatches with a clinically used pulse oximeter according to the requirements of ISO 80601-2-61. Each of the 18 young and healthy participants underwent the experimental assessment three times in randomized order-wearing Apple Watch 8, Samsung Galaxy Watch 5, or Withings ScanWatch-resulting in 54 individual experimental assessments and complete datasets. The accuracy of the SpO2 measurements was compared to that of the Radical-7 (Masimo Corporation, Irvine, CA, USA) during short-term hypoxemia induced by consecutive inhalation of three prepared gas mixtures with reduced oxygen concentrations (14%, 12%, and 10%). All three smartwatch models met the maximum acceptable root-mean-square deviation (≤4%) from the reference measurement at both normal oxygen levels and induced desaturation with SpO2 less than 90%. Apple Watch 8 reached the highest reliability due to its lowest mean bias and root-mean-square deviation, highest Pearson correlation coefficient, and accuracy in detecting hypoxemia. Our findings support the use of smartwatches to reliably detect hypoxemia in situations where the use of standard finger pulse oximeters may be limited.
Keywords: Pulmonary Disease, Chronic Obstructive; oxymetrie; kyslík; Oximetry; hypoxie; chronická obstrukční plicní nemoc; Oxygen; Hypoxia; lidé; Humans; Reproducibility of Results; reprodukovatelnost výsledků